Las personas Intersex en el Ecuador: La violencia médica una praxis que trasgrede el derecho humano a la identidad - Sánchez Espinoza, César Humberto (2022)
Intersex persons are born with a unique combination at the chromosomal and gonadal level and by the appearance of their external genitalia, which does not conform to the traditional system of male or female sex determination within the registry system, leading parents and doctors coerced by a hetero-normative-medical need to perform surgical and hormonal practices coated as “medical emergencies”. This research is based on the study of the Human Right to Identity as a starting point to demonstrate the medical violence in the health systems in Ecuador through the authoritarian determination at the time of establishing the sex of intersex people; using a qualitative approach it was possible to analyze doctrinally and legally the need for the recognition of third sex. Applying the inductive-deductive, analytical-synthetic and comparative methods, a compendium of documentation was studied that strengthens the hypothesis raised about the responsibility of the State when guaranteeing the dignity of intersex persons. The research results show that this part of the population has been forced to renounce their identity, which should allow them to individualize themselves in a personal and collective way to develop their life project, a premise that has been violated by the hegemonic power of health professionals and the family. It is concluded by pointing out that the possible paths have already been designed by other countries in the world and that in the Ecuadorian legislation the jurisdictional tools such as the Action for Protection and the Action for Non-Compliance could be considered as a legal solution after the Advisory Opinion 24-17 of the Inter-American Court of Human Rights.